Analisis Kesehatan Finansial dan Going concern PT X dan PT Y di KAP T - Sitaresmi Amarita Nirina; Nurul Fitriani; Ferry Hendro Basuki (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to analyze the financial health and evaluate the going-concern status of PT X and PT Y using financial ratio analysis and the Modified Altman Z-Score model (1995). A descriptive quantitative approach was employed, utilizing secondary data specifically audited financial statements for the 2023–2025 period obtained during an internship at Public Accounting Firm (KAP) T. The analysis involved measuring liquidity, solvency, and profitability ratios, which were then integrated with Altman Z-Score calculations to identify potential financial distress. The results indicate that both companies maintained healthy financial conditions throughout the observation period. PT X demonstrated strengths in liquidity and capital structure, with a current ratio of 2,448% and a debt-to-equity ratio of 6%, whereas PT Y exhibited superior profitability performance, recording a return on assets of 9% and a net profit margin of 26%. Altman Z-Score calculations consistently placed both PT X and PT Y in the Safe Zone, with scores of 20.30 and 18.40, respectively, in 2025. These findings suggest that neither entity showed signs of financial distress or material uncertainty casting significant doubt on their ability to continue as a going concern, thereby supporting the issuance of an Unqualified Opinion. Practically, this study demonstrates that combining financial ratio analysis with the Altman Z-Score model serves as an effective analytical procedure to support going-concern evaluations in accordance with Auditing Standards.